2018
DOI: 10.1136/bmjopen-2018-021881
|View full text |Cite
|
Sign up to set email alerts
|

Acute poisoning in Shenyang, China: a retrospective and descriptive study from 2012 to 2016

Abstract: ObjectivesUp-to-date information on the patterns of acute poisoning is crucial for the proper management of poisoning events. The objectives of this study were to analyse the characteristics of patients suffering from acute poisoning admitted to the emergency department (ED) in a tertiary medical centre in Northeast China and to compare these characteristics with those of a previous comparable study.DesignRetrospective and descriptive study.SettingData were collected from the hospital information system in She… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
65
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(91 citation statements)
references
References 46 publications
(37 reference statements)
11
65
1
1
Order By: Relevance
“…21 Moreover, people in this age group probably face failure or frustration in love or job or exams, inability to fulfill the parents' expectations. 15,19,21 However, this result was different as compared to a study conducted in Taiwan, which reported the age of 65 years or older to have the highest rate for acute poisoning. 23 This may be related to the fact that this population has a lower literacy rate, resulting in a lack of knowledge and skills related to handling poisoning agents safely.…”
Section: Discussionmentioning
confidence: 73%
“…21 Moreover, people in this age group probably face failure or frustration in love or job or exams, inability to fulfill the parents' expectations. 15,19,21 However, this result was different as compared to a study conducted in Taiwan, which reported the age of 65 years or older to have the highest rate for acute poisoning. 23 This may be related to the fact that this population has a lower literacy rate, resulting in a lack of knowledge and skills related to handling poisoning agents safely.…”
Section: Discussionmentioning
confidence: 73%
“…Acute poisoning is defined as adverse health effects due to acute exposure (less than 24 hours) to a toxic substance, medications, drug overdose, acute drug abuse problems, chemical exposures, occupational and environmental toxins, biological agents, and envenomings [1,2]. Severe acute intoxication is defined as an acute poisoning requiring technical support or close surveillance [1].…”
Section: Methodsmentioning
confidence: 99%
“…Acute poisonings are adverse health effects due to acute exposure (less than 24 hours) to a toxic substance, medications, drug overdose, acute drug abuse problems, chemical exposure, occupational and environmental toxins, biological agents, and envenomations [1,2]. Intoxications are major public and preventable health issues, which are a frequent reason for the consultation of emergency rooms [3,4] and typically represent 1-3% of all emergency department (ED) visits.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…PQ ingestion occurs frequently in the agricultural countryside, either accidentally or as a suicide attempt, thereby posing a serious public health problem. PQ accounts for an estimated 20 deaths per million person-years worldwide [ 1 3 ]. Although many investigators have attempted to find efficacious treatments for the management of acute PQ poisoning, the clinical therapeutics are still unsatisfactory, and the mortality rate remains tremendously high (50%–90%) [ 2 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%